Structurally distinct α‐synuclein fibrils induce robust parkinsonian pathology. Issue 2 (23rd October 2019) - Hayakawa, Hideki; Nakatani, Rie; Ikenaka, Kensuke; Aguirre, Cesar; Choong, Chi‐Jing; Tsuda, Hiroshi; Nagano, Seiichi; Koike, Masato; Ikeuchi, Takeshi; Hasegawa, Masato; Papa, Stella M.; Nagai, Yoshitaka; et al.
ABSTRACT: Objective: Alpha‐synuclein (α‐syn) is a major component of Lewy bodies, which are the pathological hallmark in Parkinson's disease, and its genetic mutations cause familial forms of Parkinson's disease. Patients with α‐syn G51D mutation exhibit severe clinical symptoms. However, in vitro studies showed low propensity for α‐syn with the G51D mutation. We studied the mechanisms associated with severe neurotoxicity of α‐syn G51D mutation using a murine model generated by G51D α‐syn fibril injection into the brain. Methods: Structural analysis of wild‐type and G51D α‐syn‐fibrils were performed using Fourier transform infrared spectroscopy. The ability of α‐syn fibrils forming aggregates was first assessed in in vitro mammalian cells. An in vivo mouse model with an intranigral injection of α‐syn fibrils was then used to evaluate the propagation pattern of α‐syn and related cellular changes. Results: We found that G51D α‐syn fibrils have higher β‐sheet contents than wild‐type α‐syn fibrils. The addition of G51D α‐syn fibrils to mammalian cells overexpressing α‐syn resulted in the formation of phosphorylated α‐syn inclusions at a higher rate. Similarly, an injection of G51D α‐syn fibrils into the substantia nigra of a mouse brain induced more widespread phosphorylated α‐syn pathology. Notably, the mice injected with G51D α‐syn fibrils exhibited progressive nigral neuronal loss accompanied with mitochondrial abnormalities and motor impairment. Conclusion: Our findings indicate that the structural difference of G51D α‐syn fibrils plays an important role in the rapidly developed and more severe neurotoxicity of G51D mutation‐linked Parkinson's disease. © 2019 International Parkinson and Movement Disorder Society